Analysis Of Servicescape And Customer Loyalty In Bank Syariah Mandiri (BSM ) Kcp Tebing Tinggi - Fitrianingsih Fitrianingsih; Saparuddin Siregar; Isnaini Harahap; M Ridwan (Proceeding International Seminar of Islamic Studies, 2019)
BSM is one of the Islamic banks in the City of T.Tinggi. The purpose of this study is to analyze Servicescape at Bsm KCP Tebing Tinggi and find out the form of loyalty given by customers to BSM. The location of this study is at BSM KCP Tebing Tinggi located in JL . Sudirman no 253-255 Badak Bejuang Tebing Tinggi city. This research is a qualitative descriptive study with the type of data used are primary and secondary data and data collection techniques in the form of observation, documentation and interviews. The research results show that overall Servicescape in BSM is quite good because BSM has a comfortable waiting room, service facilities that are good, employees who are amicable and nimble, office colors that are not conspicuous as well as attractive office room corner decorations and the presence of clear and easy-to-understand symbols as well as the chanting of the Koran that provides a good atmosphere of religiosity. While the loyalty that customers give to BSM is by using a variety of products offered as well as by recommending to various parties such as families, colleagues and others who are known to use BSM to save money